Unnecessary Removal of Central Venous Catheters in Cancer Patients with Bloodstream Infections. (14th January 2018) - Chaftari, Anne Marie; Hachem, Ray; Raad, Sammy; Jiang, Ying; Natividad, Elizabeth; Chaftari, Patrick; Raad, Issam
Abstract : We evaluated the rate of central venous catheter (CVC) removal in 283 cancer patients with bloodstream infections (BSIs). Removal of CVCs occurred unnecessarily in 57% of patients with non-central-line-associated BSI (non-CLABSI), which was equivalent to the rate of CVC removal in patients with CLABSIs. Physician education and safe interventions to salvage the vascular access are warranted. Infect Control Hosp Epidemiol 2018;39:222–225